(Al1−xCrx)4B6O15 (0.08 ≤ x ≤ 0.14): Metal borates catalyze the dehydration of methanol into dimethyl ether. (May 2015) - Xiang, Jia; Li, Qiaoqi; Wang, Guangjia; Ju, Jing; Cong, Rihong; Yin, Wei; Gao, Wenliang; Yang, Tao
Graphical abstract: Cr-substituted PKU-5 catalysts were performed as solid acids to catalyze the methanol dehydration at high temperatures. Various operation conditions, such as temperature, Cr 3+ content, methanol space velocity and long-time durability were also discussed in detail. Highlights: (Al1− x Cr x )4 B6 O15 (0.08 ≤ x ≤ 0.14) catalysts were prepared by a two-step route. XRD and TEM demonstrate Cr 3+ has been successively doped into the catalysts. (Al1− x Cr x )4 B6 O15 has a good catalytic activity for methanol dehydration. The catalytic activity was studied in detail under various operation conditions. Abstract: PKU-5 (Al4 B6 O15 ) is potentially a solid acid catalyst, and it possesses an interesting open-framework composed of [AlO6 ] and [B2 O5 ] groups. PKU-5 shows a high thermal stability, while no physical and chemical properties were investigated thus far, because of the difficulty in its synthesis. Cr-stabilized PKU-5 with the formula (Al1− x Cr x )4 B6 O15 (0.08 ≤ x ≤ 0.14) can be easily prepared by annealing Cr-doped PKU-1 precursors. XRD and TEM experiments demonstrate Cr 3+ has been successively incorporated into the framework of PKU-5. NH3 -TPD measurements indicate that the partial substitution of Al 3+ by Cr 3+ leads to a small change of acid sites in total amounts and distributions. Cr-PKU-5 shows a good catalytic activity for methanol dehydration from 300 to 450 °C. Other operation conditions, such as the Cr 3+ content, space velocity of methanol were also discussed in detail to evaluate its catalytic performance.